US and EC agricultural trade policies: Confrontation or negotiation? - Jimmye S. Hillman (Intereconomics, 1983)
The current American and European mutual accusations of agricultural protectionism are an obvious case of the pot calling the kettle black. What series of events led up to this confrontation? And how can the conflict situation be eased?
Keywords: 330; Agricultural Policy